Least Squares Method to Correct the Interference of Vanadium on Aluminium Determination in Vanadium Pentoxide by Spectrophotometry with Sensitization - Yan, Wenbin; Yi, Jing; Xu, Hui; He, Xinbo; Gao, Feng; Hua, Jun (Asian Journal of Chemistry, 2013)
The least square method to correction the interference of vanadium on trace amount of aluminium determination in vanadium pentoxide was studied by phenylfluorone spectrophotometry with sensitization. The sensitizing effects of various surfactants and their optimal usage conditions were examined against a blank solution at a wavelength of 560 nm. At optimal conditions, the expression governing vanadium and aluminium’s (V-Al) mixed absorbance was estimated by least squares method as: A = 0.0376CAl + 0.002902CV - 0.0015. The elimination method for this vanadium matrix, according to the aforementioned best-fit equation, and determined absorbance of V-Al allowed calculation of the aluminium concentration in a solution of known vanadium concentration. The method was thus presented as able to determine the concentration of aluminium. The experimental results showed that in a pH 10 buffer solutions, the value of e could be increased from 2.8 × 104 to 1.3 × 105 L mol cm-1 by Tween-80®, the relative deviations of the calculated results and their equivalent theoretical values were within ± 2 %.